Anti‐NMDA receptor encephalitis: clinical characteristics, predictors of outcome and the knowledge gap in southwest China. (12th November 2015) - Wang, W.; Li, J.‐M.; Hu, F.‐Y.; Wang, R.; Hong, Z.; He, L.; Zhou, D.
Abstract : Background and purpose: The aim was to analyse the clinical profiles and outcomes of patients with anti‐ N ‐methyl‐d ‐aspartate receptor (anti‐NMDAR) encephalitis in China. Methods: A retrospective study of anti‐NMDAR encephalitis in China was performed between June 2011 and June 2014. The clinical characteristics and predictors of poor outcome were determined. Results: A total of 51 patients with a definitive diagnosis of anti‐NMDAR encephalitis were included in this study. Four of them were surgically confirmed to have a neoplasm. Thirty‐two patients, amongst whom 24 were female, presented with psychiatric disorder as the initial symptom, whereas 14 patients, of whom nine were male, presented with seizure as the initial symptom ( P = 0.011). Twenty‐nine patients (56.86%) were initially misdiagnosed with psychosis, viral encephalitis or other diseases, and 58.8% of the patients experienced at least one type of complication. It typically took 3 weeks before these patients were admitted to our hospital and another 2 weeks before the correct diagnosis was made. Forty‐one patients (80%) reached a good outcome; 10 patients (20%) had a poor outcome. Older age, extended hospital stay, memory deficits, decreased consciousness, central hypoventilation, complications and abnormal cerebrospinal fluid results were associated with poor outcome ( P < 0.05). Conclusions: Female patients more frequently initially present with psychiatric disorder but male patients more frequently initially present with seizure. Patients with anti‐NMDAR encephalitis in China have a lower incidence of neoplasm. Nevertheless, this study reveals several challenges in treating anti‐NMDAR encephalitis in China that may contribute to poor outcome. Abstract : Podcast:http://player.polyv.net/videos/player.swf?vid=f6ee5715d91c5369b239824ce112c909_f